Business Development Strategy with SWOT Analysis Approach and Business Model Canvas at Wink Beauty Studio - Puspita, Astria Sandra; Muttaqin, Ridlwan (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to analyze business development strategies at Wink Beauty Studio using the SWOT Analysis and Business Model Canvas approaches. This approach aims to provide a comprehensive picture of the company's internal and external conditions and formulate the right strategy for business development. The research method used is descriptive qualitative, with data collection through in-depth interviews, observation, and documentation studies. The collected data were analyzed using a SWOT matrix to identify the strengths, weaknesses, opportunities, and threats faced by the company. The results of the SWOT analysis were then mapped into the nine elements of the Business Model Canvas, which include customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structures. The research findings show that Wink Beauty Studio has several key strengths, such as superior service quality and customer loyalty, but also faces challenges, such as intense competition and limited resources. Development opportunities lie in the growing beauty trend and the potential of the digital market. By capitalizing on internal strengths and external opportunities, the company can develop more effective strategies to expand market reach and increase profitability. This research is expected to contribute to the management of Wink Beauty Studio in formulating the right strategic steps and become a reference for other beauty business actors in developing their businesses.